NILAI-NILAI ETIKA AL-QUR'AN DAN HADIS DALAM PRAKTIK MANAJEMEN SDM - Lubis, Muhlisah; Fahrizal, Mufti (Gapenas Publisher, 2025)
This article discusses the application of ethical values contained in the Qur'an and Hadith in Human Resource Management (HRM) practices. Islamic values such as honesty, justice, trustworthiness, consultation, and benevolence are considered fundamental principles that can shape an ethical, fair, and sustainable human resource management system. This research emphasizes the importance of applying these values to create a harmonious work environment, improve employee welfare, and achieve organizational goals effectively and efficiently. This article also identifies the challenges faced in the implementation of Islamic principles in HR management, such as resistance to change, cultural differences, and limited understanding of Islamic ethics in the context of the modern workplace. Additionally, practical solutions and recommendations such as continuous training, the role of leaders as role models, and aligning policies with local regulations are proposed to address these challenges. In conclusion, the application of ethical values from the Qur'an and Hadith in HR management practices can result in organizations that are more just, productive, and oriented towards the welfare of all parties, as well as enhance the integrity and sustainability of the organization.